Sustainability assessment of an extensive cow-calf model in Mendoza, Argentina - Otta, Sebastian; Quiroz, Julio; Juaneda, Emilio; Salva, Juan; Viani, Martín; Filippini, Maria Flavia (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2016)
The sustainability of an extensive cow-calf model in General Alvear, Mendoza, was assessed. A multi-criteria method was used, using indicators based on information supplied by field visits and interviews with key actors. For this purpose, ecological, economic and social characteristics were considered. The main critical points were found in the social sphere, due to limitations on the access to public services, poor training and associativity. Regarding the economic sphere, profitability was acceptable; however, the economic risk was at the sustainability threshold due to the lack of marketing channels, high dependence on external inputs and low production efficiency. Concerning the ecological sphere, all indicators were above the sustainability threshold. Based on the research outcomes, management alternatives are proposed in order to contribute to the improvement of social conditions, range preservation and long-term economic results. In addition, the results confirm the need of assessing the sustainability of extensive cow-calf systems through appropriate indicators according to the local conditions.